2006
DOI: 10.1093/jxb/erj084
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic over-expression of the maize β-glucosidase Zm-p60.1 perturbs cytokinin homeostasis in transgenic tobacco

Abstract: The activity of the phytohormone cytokinin depends on a complex interplay of factors such as its metabolism, transport, stability, and cellular/tissue localization. O-glucosides of zeatin-type cytokinins are postulated to be storage and/or transport forms, and are readily deglucosylated. Transgenic tobacco (Nicotiana tabacum L. cv. Petit Havana SR1) plants were constructed over-expressing Zm-p60.1, a maize beta-glucosidase capable of releasing active cytokinins from O- and N3-glucosides, to analyse its potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 12 publications
0
34
0
1
Order By: Relevance
“…Recently, Kiran et al (2006) described the possible hydrolysis of CK-O-glucosides by b-glucosidase, whereby the regulation of this enzyme activity might represent another mechanism involved in the functioning of bioactive CKs in plant organogenesis. The involvement of CKX in plant organogenesis has been previously reported by Auer et al (1999), who found an increase of CKX activity during the commitment to shoot induction in petunia leaf explants in the presence of BA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Kiran et al (2006) described the possible hydrolysis of CK-O-glucosides by b-glucosidase, whereby the regulation of this enzyme activity might represent another mechanism involved in the functioning of bioactive CKs in plant organogenesis. The involvement of CKX in plant organogenesis has been previously reported by Auer et al (1999), who found an increase of CKX activity during the commitment to shoot induction in petunia leaf explants in the presence of BA.…”
Section: Discussionmentioning
confidence: 99%
“…T seeds were obtained from the T3 homozygous line of T tobacco. For a detailed description of Zm-p60.1 cloning, transformation, RT-PCR, kinetic analyses and associated properties see Kiran et al (2006). The tobacco seeds were surface-sterilized and sown in vitro on MS regulator-free medium (Murashige and Skoog 1962).…”
Section: Plant Materials and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco plants that ectopically overexpress Zm-p60.1 had CK profiles that differed from those of wildtype plants but did not exhibit any morphological changes. However, when these mutants were treated with exogenous tZ, they accumulated higher levels of active CK metabolites than wild-type plants (Kiran et al 2006). This was accompanied by the inhibition of root elongation.…”
Section: Reactivationmentioning
confidence: 99%
“…7 Therefore, the present study focused on a well-characterized member of the b-glucosidases, the maize enzyme Zm-p60.1, as a model system. Zm-p60.1 (UNI-PROT ID: P49235; PDB ID: 1HXJ) plays a key role in the targeted release of active phytohormones (cytokinins) from their inactive storage forms (cytokinin-O-glucosides), [8][9][10] and thus in the regulation of plant development. Hence, there are profound reasons for acquiring information about its structure-activity relationships, in addition to the more generally relevant information that can be obtained from studying it.…”
Section: Introductionmentioning
confidence: 99%